Equitable fraud and double liability of a debtor following notice of equitable assignment of the debt - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2019)
‘Equitable fraud’ is broader in its conception than fraud at common law. Notwithstanding ambiguities as to its precise boundaries, equitable fraud can help explain why a debtor who tenders payment to his or her creditor, despite having received notice that the money debt had been equitably assigned to an assignee, may be ordered to make payment to the assignee if the creditor-assignor were to abscond with the sums tendered, leaving the assignee out of pocket. Such liability can be explained on grounds of the debtor having committed a form of equitable fraud by dishonestly assisting in the creditor-assignor’s breach of her duties (as an equitable assignee) to the assignee. Equitable fraud can also result in liability in the debtor at common law, given the court’s power to bar a defendant to an action at law from pleading common law defences which would otherwise shield the defendant from liability at law. This article will sketch out how equitable fraud may be employed in these ways to render a debtor to be liable to pay a second time, and point out some of the implications of such reasoning.